2020
DOI: 10.3892/ol.2020.12332
|View full text |Cite
|
Sign up to set email alerts
|

Effective ferroptotic small-cell lung cancer cell death from SLC7A11 inhibition by sulforaphane

Abstract: Small-cell lung cancer (SCLC) is a highly aggressive cancer with poor prognosis, due to a lack of therapeutic targets. Sulforaphane (SFN) is an isothiocyanate derived from cruciferous vegetables and has shown anticancer effects against numerous types of cancer. However, its anticancer effect against SCLC remains unclear. The present study aimed to demonstrate the anticancer effects of SFN in SCLC cells by investigating cell death (ferroptosis, necroptosis and caspase inhibition). The human SCLC cell lines NCI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…How exactly PMA stimulates NRF2 activation is not known. However, a similar controversial regulation of NRF2 target gene subsets has also been observed with other small molecule inducers of NRF2, such as Bay 11-7085 [49] and sulforaphane [50], which stimulate ferroptosis and induce a strong upregulation of HMOX1 with concomitant downregulation of other NRF2 target genes like GPX4 and SLC7A11, respectively. Depending on the point of attack, small molecule inducers of NRF2 might therefore reveal a specific profile of NRF2 target gene regulation.…”
Section: Discussionsupporting
confidence: 62%
“…How exactly PMA stimulates NRF2 activation is not known. However, a similar controversial regulation of NRF2 target gene subsets has also been observed with other small molecule inducers of NRF2, such as Bay 11-7085 [49] and sulforaphane [50], which stimulate ferroptosis and induce a strong upregulation of HMOX1 with concomitant downregulation of other NRF2 target genes like GPX4 and SLC7A11, respectively. Depending on the point of attack, small molecule inducers of NRF2 might therefore reveal a specific profile of NRF2 target gene regulation.…”
Section: Discussionsupporting
confidence: 62%
“…SLC7A11 was overexpressed in non-small cell lung cancer (NSCLC) tissues and its overexpression was significantly correlated with poor prognosis of NSCLC patients ( Ji et al, 2018 ). Inhibition of SLC7A11 by sulforaphane or YTHDC2 (a m6A reader) induced the ferroptosis of lung cancer cells and suppressed the progression of lung cancer ( Hu et al, 2020 ; Iida et al, 2021 ; Ma et al, 2021 ). Interestingly, our results also showed that AIFM2 was overexpressed in ESCA and HNSC; however, up to now, the roles and mechanisms of AIFM2 in the progression of ESCA and HNSC were still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Various approaches have been developed to target this pathway as an anticancer strategy [ 226 , 227 , 228 , 229 , 230 , 231 ]. xCT inhibitors, such as sulfasalazine [ 232 , 233 , 234 ] and erastin [ 235 , 236 , 237 , 238 , 239 ], can reduce GSH and increase ROS in cancer cells, propagating iron-dependent lipid peroxidation that leads to tumor ferroptosis. Since inhibition of xCT alone may force cancer cells to import cysteine via other amino acid transporters such as alanine/serine/cysteine/threonine transporters (ASCT1 and ASCT2), xCT inhibitors are often used in combination with other chemotherapeutic agents or radiotherapy to overcome drug resistance.…”
Section: Emerging Ros-modulating Agents With the Potential To Enhamentioning
confidence: 99%